Effectiveness of HNO3 and NaOH Pretreatment on Lignin Degradation in Areca Leaf Sheath Fibre (Areca catechu L.) for Bioethanol Production - Wahyuti Wahyuti; Abdul Karim; Rugaiyah Andi Arfah; Muhammad Zakir; Maming Maming; Maswati Baharuddin (Automotive Experiences, 2025)
Areca leaf sheaths are underutilized waste but have a high cellulose content of 72.27%, so they can be utilized for bioethanol production. This research aims to utilize areca leaf waste for bioethanol production through acid (HNO3 5%) and alkaline (NaOH 10%) pretreatment processes, enzyme hydrolysis, and fermentation. Pretreatment using 5% HNO3 and 10% NaOH solutions is carried out because it can break down the lignin bond and release it from cellulose and hemicellulose fibers. The enzymatic hydrolysis process uses cellulase enzymes at 37 Â°C for 48 hours to produce glucose. Glucose content analysis uses the DNS method and UV-Vis spectrophotometry instruments because it is accurate and can detect glucose in low concentrations. The fermentation process is carried out using Saccharomyces cerevisiae as a fermentation microorganism because it has high efficiency in bioethanol production for a duration of 3, 5, and 7 days. Based on the results of the analysis, pretreatment with HNO3 5% solution reduced the level of lignin in areca leaf sheaths by 2.31%. Meanwhile, pretreatment using a 10% NaOH solution lowered lignin levels to 1.81%. Reduced sugar levels after hydrolysis after pretreatment with HNO3 5% and NaOH 10% were 25.08 mg/mL and 16.37 mg/mL, respectively. The highest concentration of bioethanol in the 5% HNO3 pretreatment was achieved on the 7th day at 16.75%, while that of 10% NaOH on the 5th day was 14.75%. This difference is influenced by the availability of fermentable sugars, where HNO3 substrates take longer to decompose by S. cerevisiae than NaOH substrates. Based on the analysis, the bioethanol contains ethanol, thus the areca leaf sheath fibre feedstock has the potential to assist in the advancement of a sustainable biorefinery process that can reduce dependence on fossil fuels and increase added value.